2016
DOI: 10.1021/acsnano.6b00043
|View full text |Cite|
|
Sign up to set email alerts
|

Charge-Convertible Carbon Dots for Imaging-Guided Drug Delivery with Enhanced in Vivo Cancer Therapeutic Efficiency

Abstract: Carbon dots (CDs) are remarkable nanocarriers due to their promising optical and biocompatible capabilities. However, their practical applicability in cancer therapeutics is limited by their insensitive surface properties to complicated tumor microenvironment in vivo. Herein, a tumor extracellular microenvironment-responsive drug nanocarrier based on cisplatin(IV) prodrug-loaded charge-convertible CDs (CDs-Pt(IV)@PEG-(PAH/DMMA)) was developed for imaging-guided drug delivery. An anionic polymer with dimethylma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
376
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(380 citation statements)
references
References 67 publications
3
376
0
1
Order By: Relevance
“…Discovery of graphene further advanced the study of photoluminescence of carbon‐based materials in the context of exciting applications of graphene/carbon quantum dots (CQDs) in bioimaging,160, 161, 162 drug delivery,163 photocatalysis,164, 165 electrocatalysis,165 photovoltaics,166, 167 and sensing 168. Those CQDs169 are a new form of fluorescent carbon nanostructures.…”
Section: Applications Of the Photochemical Activity Of Nanoporous Carmentioning
confidence: 99%
“…Discovery of graphene further advanced the study of photoluminescence of carbon‐based materials in the context of exciting applications of graphene/carbon quantum dots (CQDs) in bioimaging,160, 161, 162 drug delivery,163 photocatalysis,164, 165 electrocatalysis,165 photovoltaics,166, 167 and sensing 168. Those CQDs169 are a new form of fluorescent carbon nanostructures.…”
Section: Applications Of the Photochemical Activity Of Nanoporous Carmentioning
confidence: 99%
“…Yang et al succeeded in using C-dots for the in vivo studies of optical imaging with mice for animal test. Followed by these, as a result of extensive and multidisciplinary efforts, C-dots have found their place in a wide range of applications in nanoprobes [56][57][58][59][60][61][62][63][64][65][66], drug delivery [67][68][69][70][71], therapy [72][73][74][75][76], and optoelectronic devices [77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiments of charge-convertible CDs exhibited high tumor inhibition ability and low side effects as a smart nanodrug delivery with impressive therapeutic effects. 53 Bright green luminescent graphitic carbon nitride QDs (GCNQDs) doped with oxygen and sulfur were synthesized using citric acid and thiourea via a simple microwave method. The cell viability assay of GCNQDs demonstrated that GCNQDs can be used as a good and enhanced fluorescent probe for HeLa cell imaging with low cytotoxicity and high potential in bioanalysis and related research.…”
mentioning
confidence: 99%